Climate Change And The Risk Messages Of Environment: A Visual Social Semiotics Analysis Of The Malaysian And German Online Newspapers - Hasan, Nik Norma Nik (2015)
This cross-cultural study analyzes images embedded in climate change story in two online newspapers namely the Star (Malaysia), and Spigel Online (Germany) using visual social semiotics approach. The study aims to understand how journalists create and exchange meaning of environmental risks through pictures in a long-term environmental risk effect (climate change). Although, there is much debate proclaim the high risks human beings would face caused by the climate change, there is no concrete visualization to describe what climate change really is. In this sense, public who rely on the media for unobtrusive environmental information such as climate change, would tend to socially evaluate the climate change risks rightly or wrongly based on media depictions of the issue. Unlike other environmental issues such as haze, air pollution, river pollution or oil spills where the impact, effect and risk are visible, public is left (by the media) with their own imagination of risks when it comes to climate change. Hence, the ‘right’ pictures in news could help to create greater public understanding on risks. Previous research on risks mostly focused on how environmental risks being represented in the news (examining words and sentences) and claim-making made by risks actors such as scientists and government officials, however, this research takes a different approach by investigating risk via signs embedded in the pictures of environmental news. Researcher looked into caption of the picture and headline of the news to cross examine with interpersonal meta-semiotic approach as proposed by Kress and van Leeuwen (2001). Nine news samples with pictures were selected within the timeframe in between 1 July 2014 and 31 December 2014 to mark the UN Climate Change Summit which was held on 23 September 2014. Findings reveal that journalists make sense of climate change risks via pictures by making association to real environmental events. The risks are uncertain because climate change is invisible. Hence its’ risks are represented as threat and danger by the Malaysian journalists while its German counterparts depict the risk as a choice. German journalists also use the risk signs to connote economic challenges the country has been facing for the past few years.